Qualitative research in the study of leadership - Klenke, Karin; Martin, Suzanne, active 2016; Wallace, J. Randall (Emerald Group Publishing Limited, 2016)
The book is divided into four parts: (1) foundations of qualitative research methods consisting of a chapter summarizing the various qualitative paradigms and a research methods chapter illuminating various design features such as data collection and analysis, qualitative standards and ethics; (2) frequently used qualitative methods in the study of leadership designs; (3) underutilized qualitative methods; (4) three commissioned empirical studies illustrating content analysis, narrative analysis, and mixed methods study using content analysis and case study. The book also includes a chapter on the use non-textual, image-based sources of data for qualitative leadership research. Each of the methods chapters contains a number of leadership studies that have employed a given method such as case study, interviewing or phenomenology.The book is intended for students of leadership ranging from graduate students to seasoned leadership scholars. It was written with leadership practitioners in mind who wish to broaden their understanding of new developments in leadership research.